2021
DOI: 10.3389/fpsyg.2021.696263
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Evaluation of Right-Ear Advantage During Dichotic Listening

Abstract: Right-ear advantage refers to the observation that when two different speech stimuli are simultaneously presented to both ears, listeners report stimuli more correctly from the right ear than the left. It is assumed to result from prominent projection along the auditory pathways to the contralateral hemisphere and the dominance of the left auditory cortex for the perception of speech elements. Our study aimed to investigate the role of attention in the right-ear advantage. We recorded magnetoencephalography da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This reversed association between the directions of ear preference and lateralisation has been replicated consistently using various dichotic paradigms (e.g., Fernandes & Smith, 2000;Geffen & Caudrey, 1981;Hugdahl, Carlsson, Uvebrant, & Lundervold, 1997;Strauss, Gaddes, & Wada, 1987;Zatorre, 1989). Studies on healthy individuals using non-invasive functional imaging techniques confirm this general pattern on individual and group-level (e.g., Hund-Georgiadis, Lex, Friederici, & Von Cramon, 2002;Tanaka et al, 2021;Van der Haegen, Westerhausen, Hugdahl, & Brysbaert, 2013;Westerhausen, Kompus, & Hugdahl, 2014).…”
Section: Introductionmentioning
confidence: 67%
“…This reversed association between the directions of ear preference and lateralisation has been replicated consistently using various dichotic paradigms (e.g., Fernandes & Smith, 2000;Geffen & Caudrey, 1981;Hugdahl, Carlsson, Uvebrant, & Lundervold, 1997;Strauss, Gaddes, & Wada, 1987;Zatorre, 1989). Studies on healthy individuals using non-invasive functional imaging techniques confirm this general pattern on individual and group-level (e.g., Hund-Georgiadis, Lex, Friederici, & Von Cramon, 2002;Tanaka et al, 2021;Van der Haegen, Westerhausen, Hugdahl, & Brysbaert, 2013;Westerhausen, Kompus, & Hugdahl, 2014).…”
Section: Introductionmentioning
confidence: 67%
“…Additional future studies could include whether or not frankly asymmetric HL (e.g., single-sided deafness in the left versus right ear) is more strongly associated with depression and other neuropsychiatric conditions of older life. Moreover, there is a well-established ''right-ear advantage'' for speech recognition; when two distinct speech stimuli are presented to both ears simultaneously, studies have shown that listeners report stimuli more correctly from the right ear compared to the left ear (56)(57)(58)(59). Further investigation of the relative contributions of speech recognition in each ear (rather than hearing thresholds) may also elucidate any potential contributions of auditory laterality to the known association between HL and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Research has already shown that the left hemisphere controls the leading right eye, whereas the left controls the right hemisphere, which is responsible for various nonconscious processes as well as for negative feelings (Goodarzi et al, 2015;Kostandov & Arzumanov, 1986). Research also indicates that when two different speech stimuli are simultaneously presented to both ears, listeners report stimuli more correctly from the right ear than the left, indicating separate observations of left and right-ear responses to acoustic stimuli (Tanaka et al, 2021).…”
Section: Left Eye and Right Ear Subliminal Trainingmentioning
confidence: 98%